(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The paper substantiates the process of obtaining liquid fertilizers based on solutions of potassium sulfate, ammonium nitrate, urea, copper sulfates, and monoethanolammonium. The dependence of changes in the physicochemical properties of solutions on the composition of the components is studied. Based on the data obtained, diagrams of "composition-properties" are constructed.